Kekayaan Arsitektural Kampung Arab di Palembang (Kasus Kampung Al Munawar dan Kampung Assegaf) - Johannes Adiyanto; Anjuma Perkasa Jaya; Dessa Andriyali Armarieno (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2022)
Palembang is a historic city in Indonesia. Palembang serves as a port and a trading hub in addition. The Hadrami, who hailed from Hadramaut, were one tribe of traders who subsequently made Palembang their home. The Hadrami immigrants reside in the two historic villages of Al Munawar and Assegaf. In this study, architectural components in these two villages are used as signs that can be interpreted based on their denotation and connotation. This research method is known as semotics in architecture. This essay demonstrates how the socioeconomic proximity of the villagers to the ruling authorities at the time—namely the Palembang Darussalam Sultanate and the Dutch East Indies—is related to the shape of the buildings in these two villages. The result of the result would be a basis of next studies and also program of city development, especially in Palembang City.